2020
DOI: 10.1007/s11252-020-01061-8
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization alters the abundance and composition of predator communities and leads to aphid outbreaks on urban trees

Abstract: Urbanization can affect arthropod abundance in different ways. While species with narrow habitat range and low dispersal ability often respond negatively to urban environments, many habitat generalist species with good dispersal ability reach high densities in city centers. This filtering effect of urban habitats can strongly influence predator-prey-mutualist interactions and may therefore affect the abundance of predatory and phytophagous species both directly and indirectly. Here, we assessed the effect of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…We expect the effect sizes to positively correlate with the HFI, indicating that as the intensity of anthropogenic pressure increased, the magnitude of change to predation would increase. Predator diversity and density, and thus predation rates and prey selection, are correlated with the components used to calculate the HFI, such as human population density and land-use conversion, underpinning our expectation that the degree of urbanization would explain variation in predator diet effect sizes (Eötvös et al, 2018;Korányi et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…We expect the effect sizes to positively correlate with the HFI, indicating that as the intensity of anthropogenic pressure increased, the magnitude of change to predation would increase. Predator diversity and density, and thus predation rates and prey selection, are correlated with the components used to calculate the HFI, such as human population density and land-use conversion, underpinning our expectation that the degree of urbanization would explain variation in predator diet effect sizes (Eötvös et al, 2018;Korányi et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Since ruderal grassland, independent of urban settlement, had a higher disturbance intensity, Sattler et al (2011) suggested that such grasslands might have fewer, but more resilient arthropod species. Rangelands exhibited higher diversity than the ruderal and fragmented grasslands, probably due to less disturbance and fragmentation as well as the larger availability of structural habitat variation provided in more natural areas (Mata et al 2017, Botha et al 2018Koranyi et al 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Adams et al (2020) reported that urban arthropods are affected by a mixture of fine, local, and landscape-scale mechanisms. Thus vegetation diversity, cover, structure, frequency of mowing at a fine scale (Lowe et al 2017(Lowe et al , 2018Philpott et al 2020;Koranyi et al 2021), the mosaic of the urban green spaces within a city, level of urbanization and isolation at a local scale (Delgado de la Flor et al 2020;Fenoglio et al 2020;Rocha and Fellowes 2020) and even rainfall (Lowe et al 2017) at a regional level can influence arthropod abundance, richness and communities such as the ones included in this study. Furthermore, different species react differently to different environmental disturbances and mechanisms (Rocha and Fellowes 2020), thus influencing the patterns and trends we observe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine of these species still occurred in the region in 1990–2020. Therefore, landscape transformation and intensive recreational use for several decades have not caused the large-scale extinction of native ladybird species, corresponding to the fact that many ladybird species successfully adapt to urbanization [ 46 ].…”
Section: Discussionmentioning
confidence: 99%